Effect of School Based Cognitive behavioral Therapy on Multidimensional Level of Anxiety among Adolescents with Intellectual Disability: A Randomized Controlled Trial - Neji, Hope Amba; Ofem, Usani Joseph; Agbor, Comfort Nkongho; Emmanuel, Ahueansebhor; Okaforcha, Choice Chima; Okorn, Obeten Okoi; Nwannunu, Blessing Iheoma; Madukwe, Esther; Nkechi, Ezeaku Stella; Chinenye, Okaforcha Patrick; Bayim, Beatrice Arisa; Okoye, Anthony Chinyere; et al. (Journal of Intellectual Disability - Diagnosis and Treatment, 2025)
Introduction: Anxiety is a common issue faced by adolescents with mild intellectual disabilities, but there’s still limited research on interventions designed specifically for them. While Cognitive Behavioral Therapy (CBT) has proven effective for managing anxiety in the general population, we need to understand better how well it works for young people with intellectual disabilities. Purpose/Objectives: This study set out to explore how effective school-based CBT is at reducing different types of anxiety in adolescents with mild intellectual disabilities. It also looked at whether gender and age play a role in how well the therapy works. Methodology: We carried out a pretest-posttest randomized controlled trialstudy with 150 adolescents randomly placed into either a CBT treatment group or a control group. The anxiety measurement tool was carefully adapted to fit the cultural context and tested to ensure it was reliable. We analyzed the results using Multivariate Analysis of Covariance (MANCOVA), while accounting for anxiety levels before treatment. Results: The findings showed that CBT significantly eased symptoms across five types of anxiety: separation anxiety, social phobia, generalized anxiety, panic anxiety, and obsessive-compulsive disorder. The therapy worked equally well for both boys and girls. Most age groups responded similarly, but there was a notable difference in how separation anxiety improved, suggesting that a young person’s developmental stage may affect their response to CBT. Conclusion/Implications: These results reinforce that cognitive-behavioral therapy can be effective for adolescents with mild intellectual disabilities. They also highlight the importance of adjusting therapy to fit different developmental stages. Overall, the study encourages incorporating CBT into school mental health programs with tailored support to best meet the needs of this vulnerable group, ensuring that treatment is both practical and fair for all.